Novo gerencialismo e o gerente educacional no contexto do PROGEPE: uma análise na ótica da governamentalidade - Rocha, Paula Rejane Lisboa da (2017)
This thesis discusses the formation of the school manager based on the Program of Continuing Training of School Managers of Pernambuco - PROGEPE. In order to do so, the effects of this policy on the management and training of the responsible and self-responsible school manager were analyzed, due to the success of management by results, policy implemented by the Educational Management Modernization Program (PMGE / ME) . This research is based on a qualitative approach, where the discourses analyzed in the “Foucaultian” perspective were extracted from the PROGEPE documents themselves and from the data collected through semi-structured interviews with managers / managers from the program. The theoretical reference was formed, in particular, with the contributions of Michel Foucault on the government of himself and others, a discussion pertinent to the concept of governmentality. The research pointed out that, under the influence of the managerial management implanted in Pernambuco, expensive concepts for democratic management, such as: participation, autonomy, decentralization, quality among others, have been discursively restaigned, to attend to the conservative, excluding and authoritarian productivist logic of educational management, based on results. Another important point is the concern of the managers to raise the goals in the external evaluations, especially of the Educational Evaluation System of Pernambuco (SAEPE), which allows the formation of a performance culture, where the value of the individual, as a professional, becomes proportional to their numerical performance in school. Finally, the research emphasizes that, according to the policy adopted by the government of Pernambuco, in relation to school management, the manager's training gains centrality. However, the democratic manager has lost space for the formation of the school manager, increasingly responsible and self-responsible, for the performance of his school, generating a certain exhaustion.